Does geography play a role in takeovers? Theory and Finnish micro-level evidence - Petri Böckerman; Eero Lehto (European Regional Science Association (ERSA), 2004)
This study explores domestic inter-regional merger flows. Theoretical considerations based on monitoring are developed. The empirical part of the study is based on the comprehensive public data on domestic mergers and acquisitions that is matched to the micro-level data sources maintained by Statistics Finland in order to obtain several variables that help to characterize the companies involved. The Finnish evidence reveals that geographical closeness matters a great deal for inter-regional merger flows. This means that a great number of domestic mergers occur within narrowly defined regions. Domestic merger flows substantially reinforce the core-periphery dimension. The most important finding from matched data is that the strong ability by an acquiring company to monitor the target (measured by the knowledge embodied in human capital) is able to support mergers that occur across distant locations, other things being equal. Geographical closeness and proximity across industries are not related, based on the Finnish evidence.
Keywords: 330